A novel pathway activated by somatostatin receptor type 2 (SST2): Inhibition of pituitary tumor cell migration and invasion through cytoskeleton protein recruitment. Issue 9 (20th December 2017) - Peverelli, E.; Giardino, E.; Treppiedi, D.; Catalano, R.; Mangili, F.; Locatelli, M.; Lania, A.G.; Arosio, M.; Spada, A.; Mantovani, G.
Abstract : The pharmacological therapy of GH‐secreting pituitary tumors is based on somatostatin (SS) analogs that reduce GH secretion and cell proliferation by binding mainly SS receptors type 2 (SST2). Antimigratory effects of SS have been demonstrated in different cell models, but no data on pituitary tumors are available. Aims of our study were to evaluate SST2 effects on migration and invasion of human and rat tumoral somatotrophs, and to elucidate the molecular mechanism involved focusing on the role of cofilin and filamin A (FLNA). Our data revealed that SST2 agonist BIM23120 significantly reduced GH3 cells migration (−22% ± 3.6%, p < 0.001) and invasion on collagen IV (−31.3% ± 12.2%, p < 0.01), both these effects being reproduced by octreotide and pasireotide. Similar results were obtained in primary cultured cells from human GH‐secreting tumors. These inhibitory actions were accompanied by a marked increase in RhoA/ROCK‐dependent cofilin phosphorylation (about 2.7‐fold in GH3 and 2.1‐fold in human primary cells). Accordingly, the anti‐invasive effect of the SS analog was mimicked by the overexpression in GH3 cells of the S3D phosphomimetic cofilin mutant, and abolished by both phosphodeficient S3A cofilin and a specific ROCK inhibitor that prevented cofilin phosphorylation. Moreover, FLNA silencing and FLNA dominant‐negative mutants FLNA19‐20 and FLNA21‐24 transfection demonstrated that FLNA plays a scaffold function for SST2‐mediated cofilin phosphorylation. Accordingly, cofilin recruitment to agonist‐activated SST2 was completely lost in FLNA silenced cells. In conclusion, we demonstrated that SST2 inhibits rat and human tumoral somatotrophs migration and invasion through a molecular mechanism that involves FLNA‐dependent cofilin recruitment and phosphorylation. Abstract : What's new? The pharmacological therapy of growth hormone (GH)‐secreting pituitary tumors is based on somatostatin (SS) analogs that reduce GH secretion and cell proliferation by binding mainly SS receptors type 2 (SST2). Anti‐migratory effects of SS have been demonstrated in different cell models, but so far no data in pituitary tumors are available. Our study reveals a novel antitumoral activity of SST2 by demonstrating that SST2 inhibits rat and human pituitary tumor cells migration and invasion. The molecular mechanism involves the recruitment to agonist‐activated SST2 of a protein complex that through FLNA scaffold function regulates cofilin activity and consequently actin cytoskeleton remodeling.